Modelling Exposure to Risk of Experiencing Discrimination in the Context of Endogenous Ethnic Identification - Boyd Hunter; Monica Howlett; Nicholas Biddle (Institute for the Study of Labor (IZA), 2014)
Gneezy et al. (2012) uses attribution theory from the psychology literature to argue that when the object of discrimination is a matter of choice (e.g. sexual orientation), observed discrimination may motivated by animus, which exacerbates or intensifies the emotional response to the object of discrimination. This paper builds on this insight based on the understanding that ethnicity is largely a social construct where individuals can often choose to identify with an ethnic group that may be the object of discrimination. A theoretical model is constructed that predicts that the choice to identify interacts with the observability of ethnicity, and the exposure to situations where there is a risk of discrimination, to produce a non-linear relationship with reported episodes of discrimination. Evidence from the 2008 National Aboriginal and Torres Strait Islanders Social Survey (NATSISS) is presented that is consistent with the predictions of this theory.
Keywords: J15; J71; Z13; 330; discrimination; racial bias; identity; social networks